Gas exchanges and production of colored cotton irrigated with saline water at different phenological stages - Soares, Lauriane; Fernandes, Pedro; Lima, Geovani; Suassuna, Janivan; Pereira, Rennan (Revista Ciência Agronômica, 2018)
Scarcity of good-quality water is a limiting factor for irrigated agriculture, especially in semi-arid regions, which leads to the use of water with high salt content to irrigate crops. Therefore, this study aimed to evaluate physiological aspects and production of colored cotton genotypes under saline stress, during the different development stages and under conditions of low and high salinity. The experiment was conducted using a randomized block design, with a 3 × 7 factorial scheme and three replicates. Treatments corresponded to three colored cotton genotypes irrigated with low-salinity water (0.8 dS m-1) and high-salinity water (9.0 dS m-1): T1-A1B1C1, T2-A2B1C1, T3-A1B2C1, T4-A1B1C2, T5-A2B1C2, T6-A2B2C1 and T7-A1B2C2 (A1, B1 and C1: without salinity and A2, B2 and C2: with salinity; in the vegetative, flowering and fruiting stages, respectively). Among the genotypes, BRS Rubi was the most sensitive to irrigation water salinity, regardless of development stage. Successive application of saline water at the flowering and boll formation stages led to drastic reduction in physiological aspects of the crop, with recovery of the plants after the stress was interrupted. Saline water irrigation at initial development stages can be used in the cotton crop for reducing the average time to the beginning of flowering. Seed cotton production was more affected by application of saline water at the flowering and boll formation stages.